The interaction of occupational noise exposure with the cardiovascular risk factors - S. Seydi Joughan; M. Hosseininejad; S. Mohammadi; L. Khedmati Hampa; N. Kassiri (Acta Biomedica Scientifica, 2025)
Rational. Occupationalnoiseposesasignificantoccupationalhazard, affecting a large portion of the global population. The correlation between cardiovascular risk factors and noise exposure has been examined, and conflicting findings have been found.The aim. This study aimed to explored the association between occupational noise and cardiovascular risk factors among word related noise-exposed laborers.Methods. A cross-sectional study was conducted among 495 workers at a home appliance manufacturing factory. Participants are divided in two groups including workers exposed to noise levels above 85 dB and below 85 dB at work. Demographic information, audiometric tests, blood pressure tests, and lipid profile testing collected from the occupational health files. To evaluate the association between noise exposure andcardiovascular risk factors, themultivariable logistic regression analyzeswereused. Results. Our finding revealed significant correlation between exposure to noise above the 85 db and elevated levels of fasting blood sugar (FBS), triglyceride (TG), low-density lipoprotein (LDL), physical activity and high diastolic blood pressure. Following logistic regression to remove the impact of confounding variables, relationship between FBS, LDL, TG and physical activity remained statistically significant.Conclusions. The current investigation shows the correlation between exposure to noise above the permissible limit and the risk factors of cardiovascular diseases, especially FBS, LDL, and TG.